Acute and chronic effects of Rhaponticum carthamoides and Rhodiola rosea extracts supplementation coupled to resistance exercise on muscle protein synthesis and mechanical power in rats. Issue 1 (16th November 2020) - Roumanille, Rémi; Vernus, Barbara; Brioche, Thomas; Descossy, Vincent; Van Ba, Christophe Tran; Campredon, Sarah; Philippe, Antony G.; Delobel, Pierre; Bertrand-Gaday, Christelle; Chopard, Angèle; Bonnieu, Anne; Py, Guillaume; et al.
Abstract: Background: Owing to its strength-building and adaptogenic properties, Rhaponticum carthamoides ( Rha ) has been commonly used by elite Soviet and Russian athletes. Rhodiola rosea ( Rho ) is known to reduce physical and mental fatigue and improve endurance performance. However, the association of these two nutritional supplements with resistance exercise performance has never been tested. Resistance exercise is still the best way to stimulate protein synthesis and induce chronic muscle adaptations. The aim of this study was to investigate the acute and chronic effects of resistance exercise coupled with Rha and Rho supplementation on protein synthesis, muscle phenotype, and physical performance. Methods: For the acute study, fifty-six rats were assigned to either a trained control group or one of the groups treated with specific doses of Rha and/or Rho . Each rats performed a single bout of climbing resistance exercise. The supplements were administered immediately after exercise by oral gavage. Protein synthesis was measured via puromycin incorporation. For the chronic study, forty rats were assigned to either the control group or one of the groups treated with doses adjusted from the acute study results. The rats were trained five times per week for 4 weeks with the same bout of climbing resistance exercise with additionals loads. Rha + Rho supplement was administered immediately after each training by oral gavage. Results: The findings of the acute study indicated that Rha and Rha + Rho supplementation after resistance exercise stimulated protein synthesis more than resistance exercise alone ( p < 0.05). After 4 weeks of training, the mean power performance was increased in the Rha + Rho and Rha -alone groups ( p < 0.05) without any significant supplementation effect on muscle weight or fiber cross-sectional area. A tendency towards an increase in type I/ type II fiber ratio was observed in Rha/Rho -treated groups compared to that in the trained control group. Conclusion: Rhodiola and Rhaponticum supplementation after resistance exercise could synergistically improve protein synthesis, muscle phenotype and physical performance.